2009
DOI: 10.1007/s11426-009-0288-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonding of single acetic acid with water molecules in dilute aqueous solutions

Abstract: In separation processes, hydrogen bonding has a very significant effect on the efficiency of isolation of acetic acid (HOAc) from HOAc/H 2 O mixtures. This intermolecular interaction on aggregates composed of a single HOAc molecule and varying numbers of H 2 O molecules has been examined by using ab initio molecular dynamics simulations (AIMD) and quantum chemical calculations (QCC). Thermodynamic data in aqueous solution were obtained through the self-consistent reaction field calculations and the polarizable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It is important that the scCO 2 in this study is water-saturated, as the addition of a water cosolvent to scCO 2 fluids enhances their solvation properties . The organic acids are hydro- and CO 2 -philic, and experience binding interactions with both components of the wet scCO 2 fluid. , In fact, once the organics are scavenged by the scCO 2 , they too act as cosolvents, increasing the solubilities of organics in the fluid. ,,, Due to the notoriously poor ability of CO 2 to solvate inorganic metal complexes ,, and the lack of in situ verification of the measurements, the lack of evidence for Ca or Mn in the reacted samples from EXP 2 and EXP 3 is not surprising. Furthermore, we are not aware of any studies that have measured the solubility of metal–acetate complexes in CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important that the scCO 2 in this study is water-saturated, as the addition of a water cosolvent to scCO 2 fluids enhances their solvation properties . The organic acids are hydro- and CO 2 -philic, and experience binding interactions with both components of the wet scCO 2 fluid. , In fact, once the organics are scavenged by the scCO 2 , they too act as cosolvents, increasing the solubilities of organics in the fluid. ,,, Due to the notoriously poor ability of CO 2 to solvate inorganic metal complexes ,, and the lack of in situ verification of the measurements, the lack of evidence for Ca or Mn in the reacted samples from EXP 2 and EXP 3 is not surprising. Furthermore, we are not aware of any studies that have measured the solubility of metal–acetate complexes in CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, chloroform would be the preferred choice for the extraction of alcohols and furans from the biooil aqueous phase. Levoglucosan and organic acids such as acetic acid can form hydrogenbonding with water in the bio-oil aqueous phase [6,43]. Although chloroform has a high polarity, it barely breaks the hydrogen bond in extraction.…”
Section: Effects Of Solvents On the Separation Of 15 Individual Chemimentioning
confidence: 99%
“…[23][24][25] Gao et al 26 investigated the H-bonding in the mono-and dihydrates of a single HAc molecule from a density functional theory with three large basis sets. Pu et al [27][28][29] reported more hydrates combined quantum chemical calculations (QCC) and ab initio molecular dynamics simulations (AIMD). These works suggested that the structure of the favorable hydrates involves head-on rings (see Section 2 for the definition).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the presence of the monohydrates and dihydrates of acetic acid, trifluoroacetic acid, and propionic acid was determined by the high-resolution microwave spectroscopic. Gao et al investigated the H-bonding in the mono- and dihydrates of a single HAc molecule from a density functional theory with three large basis sets. Pu et al reported more hydrates combined quantum chemical calculations (QCC) and ab initio molecular dynamics simulations (AIMD). These works suggested that the structure of the favorable hydrates involves head-on rings (see Section 2 for the definition).…”
Section: Introductionmentioning
confidence: 99%